Design of Virtual Reality System for 3D Visualization and Interaction : https://doi.org/10.69692/SUJMRD0901149 - Kounlaxay, Kalaphath; Manyvanh, Vialakone; Pathoumxay , Sommany; Sengdala, Sinlapaxay; Soo Kyun, Kim (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
Nowadays, a virtual environment or metaverse environment is becoming more popular and can be used for various purposes. There are many computer games and more applications for them such as for training, learning and planning. Currently the presentations of 3-Dimensional (3D) models using mixed reality (MR) technology can be used to avoid misinterpretations of oral and 2-Dimensional (2D) model presentations. As an independent concept and MR applications, MR combines the best of virtual reality (VR) and augmented reality (AR). Therefore, this research aimed to present the descriptions of MR systems, which include its devices, applications, literature reviews and create 3D models that were then implemented in Unity 3D using VR applications for 3D architectural visualization. In addition, the assessment results of the VR application showed that the mean score of 2.85 and 3.45 (“neutral”) indicated that the VR application was a new one for the students and they had never used it before, but they certify that learning with VR is not as difficult as with other simulations. The mean scores of 4.55, 4.70, and 4.75 (“strongly agree”) indicated that the use of the VR application’s 3D objects in the scene was beautiful, clear, and realistic. Besides, the student also enjoyed the immersive experience and the learning was very interesting and they felt that they were in the real world.